Ownership and control in the entrepreneurial firm: an international history of private limited companies - Timothy W. Guinnane; Ron Harris; Naomi R. Lamoreaux; Jean-Laurent Rosenthal (Yale University, Economic Growth Center, 2007)
We use the history of private limited liability companies (PLLCs) to challenge two pervasive assumptions in the literature: (1) Anglo-American legal institutions were better for economic development than continental Europe's civil-law institutions; and (2) the corporation was the superior form of business organization. Data on the number and types of firms organized in France, Germany, the UK, and the US show that that the PLLC became the form of choice for small- and medium-size enterprises wherever and whenever it was introduced. The PLLC's key advantage was its flexible internal governance rules that allowed its users to limit the threat of untimely dissolution inherent in partnerships without taking on the full danger of minority oppression that the corporation entailed. The PLLC was first successfully introduced in Germany, a code country, in 1892. Great Britain, a common-law country followed in 1907, and France, a code country, in 1925. The laggard was the US, a common-law country whose courts had effectively killed earlier attempts to enact the form.
Keywords: N8; G3; O16; K22; 330; limited company; partnership; corporation; legal regime; common law; civil law